On the grounds of differentiated professional – work teaching in assisted boarding school - Šliosbergas , L. (Psichologija, 1971)
The author justifies the individualization of labor education of mentally retarded children based on the long-term observation of students in Vilnius boarding school No. 2. The article presents observation data of 211 students who work in school.